Modification of photosensitive resin with fumed silica - Zhao, Jie; Song, Tao; Chu, Wei; Wang, Yingying; Bi, Lunan; Han, Zhuoqun; Li, Ling (Polimery, 2023)
The effect of fumed silica (3 and 5 wt%) on the structure, viscosity, tensile and flexural properties, and hardness of photosensitive acrylic resins used for 3D printing was investigated. The optimal set of functional properties was obtained with a silica content of 3 wt%. In this case, the resin had the appropriate viscosity, degree of cross-linking, hardness (90 ShD), tensile strength (47 MPa) and flexural strength (96 MPa). The obtained results indicate that the addition of silica effectively reinforce the resin.